Передача знаний как составляющая корпоративного имиджа компании - Коваль, А. В.; Молодожен, А. А. (ХНУРЭ, 2012)
This paper considers the issue of knowledge transfer as part of the corporate image of the corporation. We present a scheme of transfer knowledge and experience within the organization. It also describes the basic methods – the transfer of authority, training and mentoring.